Manajemen Laba dan Kinerja Operasional Sebelum dan Sesudah IPO Bursa Efek Indonesia - Nany, Magdalena; Prasetyaningrum, Murni; Pratama, Daniel Budi; Triana, Yovan (Universitas Indraprasta PGRI, 2023)
The corporate perform IPO to get any additional fund for corporate development. In order to attract the investors, manager can report higher profit that said as earnings management. Earnings management occurs when managers use considerations in financial reporting, and form transactions to change financial statements with the aim of manipulating the amount of profit to some stakeholders about the underlying economic performance of the company. The purpose of this research is to examine earnings management surrounding IPO. The purpose of this research is also to examine the differences in financial performance before and after the IPO. This study uses secondary data of financial statements that did an IPO in 2017-2020, from 180 companies. Based on the testing conducted by wilcoxon signed test, it was found that there were no significant differences between earnings management and financial performance surrounding IPO. The company has great optimism because the company's financial statement information already shows a good financial position without having to do earnings management so that it can attract the attention of investors at the initial public offering to invest their funds by buying the company's shares. The practice of earnings management carried out before conducting an IPO has no effect on the rate of return on assets even though in practice the profit management carried out is an effort to make the company's profits look satisfactory.